Cardiac strangulation, a rare complication of epicardial pacemaker leads during growth. Issue 3 (March 1997) - Eyskens, B.; Mertens, L.; Moerman, P.; Ector, H.; Daenen, W.; Gewilling, M.
Abstract : A six year old boy with an epicardial pacing lead since infancy presented with thoracic pain triggered by movement. The pain was thought to be musculoskeletal, but two weeks later he collapsed and died in ventricular fibrillation. Necropsy showed strangulation of the ventricular apex by the epicardial lead.